Complement component C7 is a plasminogen-binding protein. - Reinartz, Jeannette; Hänsch, Gertrud Maria; Kramer, Michael D. (The journal of immunology, 1995)
Ab deposition, whether by reaction with the specific Ag or by preformed immune complexes, is followed by activation and deposition of complement components. Tissue destruction is observed in the Ab- and complement-induced lesions. The proteolytic enzyme plasmin is thought to participate in the Ab- and complement-mediated organ pathology. Plasmin is generated from plasma-derived plasminogen by cell-derived plasminogen activators (PAs). Two types of PAs are known, urokinase-type PA (uPA) and tissue-type PA (tPA). We investigated whether the PA system and the complement system can interact to promote local plasmin generation. Among the terminal complement components C5b6, C7, C8, and C9, the nonenzymatic component C7 is a plasminogen-binding protein. Radioligand binding studies revealed that the isolated component, as well as C7 after its incorporation into the terminal complement complex C5b-9, can bind plasminogen. Binding was inhibited by the lysine analogues 6-aminohexanoic acid and tranexamic acid, implicating the lysine binding sites of plasminogen into the binding interaction. tPA-mediated plasminogen activation was enhanced in the presence of C7. Based on these findings, an interaction is proposed between the complement system and the plasminogen activator system; a mechanism that may focus plasmin activity to structures that have been tagged by Ab and complement deposition.